Inovasi Rolade Ikan Patin (Pangasius sp.) Dengan Kulit Berbahan Daun Singkong Dan Agar-agar - Mohammad Afriyan Anggadiotama; Ita Fatkhur Romadhoni; Lilis Sulandari; Asrul Bahar (Journal of Creative Student Research, 2023)
Rolade its a dish that is rarely consumed by the public because the manufacturing process is complicated and cassava leaves are vegetables that have coarse fiber, these two problems are the goal of this research which is an experiment in making cassava leaves and agar-agar as skin for making catfish rolade. This research uses a comparison of the number of cassava leaves and agar-agar with 3 treatments namely (80 grams: 4 grams), (80 grams: 6 grams), and (80 grams: 8 grams). Data collection was carried out by observation method through organoleptic test. Organoleptic test results data were processed by one way ANOVA test and Duncan's advanced test. To determine the content of proximate and vitamin A, laboratory tests were carried out and the selling price was determined for 250 gram packages. The results showed: 1)Catfish rolls with skin made from cassava leaves and agar-agar produced a product with a ratio of the amount of cassava leaves and agar-agar 80 grams: 6 grams. 2)Based on laboratory test results, the best sample per 100 grams contains Vitamin A 119.65 mg, Water 30.55%, Protein 18.05%, Fat 19.52%, Carbohydrates 30.04% and Ash 1.92% . 3)The selling price of catfish rolls with skin made from cassava leaves and agar is known to be Rp. 20,000 per 250 gram pack.